Chinese Aid and Health at the Country and Local Level - John Cruzatti C.; Axel Dreher; Johannes Matzat (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We investigate whether and to what extent Chinese development finance affects infant mortality, combining 92 demographic and health surveys (DHS) for a maximum of 53 countries and almost 55,000 sub-national locations over the 2002-2014 period. We address causality by instrumenting aid with a set of interacted variables. Variation over time results from indicators that measure the availability of funding in a given year. Cross-sectional variation results from a sub-national region's “probability to receive aid.” Controlled for this probability in tandem with fixed effects for country-years and provinces, the interactions of these variables form powerful and excludable instruments. Our results show that Chinese aid increases infant mortality at sub-national scales, but decreases mortality at the country-level. In several tests, we show that this stark contrast likely results from aid being fungible within recipient countries.
Keywords: I15; F35; 330; health aid; fungibility; infant mortality